Assessing the impact of land use and changes in land cover related to carbon storage by linking trajectory analysis and InVEST models in the Nandu River Basin on Hainan Island in China - Gong, Wenfeng; Duan, Xuanyu; Mao, Mingjiang; Hu, Jihan; Sun, Yuxin; Wu, Genghong; Zhang, Yangyang; Xie, Yidan; Qiu, Xincai; Rao, Xiaodong; Liu, Tiedong; Liu, Tao (Frontiers in Environmental Science, 2022)
This study aims to evaluate the effects of the spatiotemporal patterns of land-use and land-cover (LULC) changes on the dynamics of carbon storage in a tropical region of China by linking the trajectory analysis of LULC changes and the InVEST model. Based on remote sensing (RS), geographic information system (GIS) and change trajectories, the spatiotemporal evolution of LULC changes was explored. This evolution could be coupled with the spatiotemporal LULC change trajectories and the InVEST model for the quantitative study of the spatial distribution and temporal variation in regional carbon stocks. The results showed that during the 2000-2020 period, the built-up land continually increased to 206.55 km2 through urban expansion, and forestland became the dominant type of land, with an area of 357.39 km2. In addition to the change in land use, the carbon storage in the study region increased to 4.87 Tg C. The anaphasic trajectory had the largest area ratio at 7.05% in the total area, while the prophasic trajectory contributed to the largest increase in carbon storage, 5.87 Tg C. Moreover, the repetitive trajectories had no impact on carbon sinks and sources, whereas the anaphasic trajectory and the continual trajectory imposed passive impacts on carbon storage. These advances in research underpin scientific efforts to improve the understanding of the relationship between the optimization of land-use structure and patterns and the carbon storage service in the Nandu River Basin.